A polymer chip-integrable piezoelectric micropump with low backpressure dependence1. Issue 62 (8th July 2015) - Conde, A. J.; Bianchetti, A.; Veiras, F. E.; Federico, A.; Cabaleiro, J. M.; Dufva, M.; Madrid, R. E.; Fraigi, L.
<x xml:space="preserve">Abstract</x> A polymer piezoelectric micropump fabricated with conventional machining methods that can be embedded in laminated microfluidic chips.